Desempenho de painéis Mdp produzidos com diferentes teores de adesivo cardanol-formaldeído associado á adição de nanopartículas de lignina - Trindade, Edgard Geraldo Bertoli (2025)
Cardanol, a phenolic compound derived from cashew nut processing, has shown potential for synthesizing cardanol-formaldehyde adhesives with low formaldehyde emissions. These adhesives not only utilize cardanol as a renewable resource, contributing to the valorization of waste, but also exhibit promising properties for wood panel production. However, there is still a need to improve the technological performance of cardanol-formaldehyde adhesives. The incorporation of lignin nanoparticles appears as a promising method for modifying phenolic adhesives, being associated with improvements in mechanical and thermal properties and reduction of formaldehyde emissions. Thus, the objective was to evaluate the quality of MDP panels produced with Pinus oocarpa particles bonded with three levels of cardanol- formaldehyde adhesive (6, 9 and 12%) combined with three additions of lignin nanoparticles (0, 1 and 2%). The panels were produced with a nominal density of 0.75 g/cm3. The adhesive properties evaluated were viscosity, pH, gel time, and solids content. The panels were evaluated for their physical properties (apparent density, compaction ratio, moisture content, water absorption, thickness swelling, thickness swelling recovery rate and thermal conductivity), mechanical properties (static bending strength and internal bond), and chemical properties (free formaldehyde emission). Three repetitions were considered for each treatment. For statistical analysis, a Completely Randomized Design with a double factorial arrangement was used, considering as the first factor the cardanol-formaldehyde adhesive concentrations and as the second factor the lignin nanoparticle additions. The obtained values were subjected to analysis of variance (ANOVA at 5%) and Tukey’s test (5%). The addition of lignin nanoparticles increased the adhesive’s pH and gel time, while decreasing solids content and viscosity. Rheological analysis showed that the cardanol-formaldehyde adhesive has an atypical relationship with temperature, exhibiting extremely high viscosity at room temperature (25°C) and an ideal viscosity for application close to the synthesis temperature (90°C). Regarding main effects, the best physical and mechanical performance was related to the 12% adhesive content and 0% nanoparticle addition. The addition of lignin nanoparticles only improved thermal conductivity. Formaldehyde emissions increased with adhesive content and nanoparticle addition. However, upon dissecting the adhesive content factor by lignin nanoparticle addition, a decrease in formaldehyde emission was observed with increasing adhesive content, but only at 2% nanoparticle addition. All treatments were classified as E1 (< 8.0 mg/100 g of dry panel) for formaldehyde emission according to NBR 14810-2. Applications with 12% adhesive and 0% or 1% nanoparticle addition showed excellent performance, fitting the P2 class (interior use in dry environments) of NBR 14810-2. These results indicate the high potential of cardanol-formaldehyde to replace synthetic urea-formaldehyde adhesive in the production of MDP particleboards.